Students’ Perception of Using Machine Translation: A Survey of Indonesian EFL Undergraduate Students - Rahmawati, Siti; Baihaqi, Akhmad; Imtihanudin, Dede (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2025)
The purpose of this study is to find out how students perception about using DeepL for machine translation during the translation process. The study used a qualitative survey method. Students in the fourth semester of the English Education Department at Sekolah Tinggi Keguruan dan Ilmu Pendidikan Syekh Manshur, Indonesia, are given a questionnaire via Google Form in order to collect information about their perception about the usage of machine translation. According to the range of students' perception scores, the usage of machine translation is classified as positive (high) by the results, which showed that the mean score of the questionnaire was 70%. Based on the result, students believe that machine translation is crucial for their English studies. This is because machine translation can improve students' vocabulary and grammar comprehension, so making it a useful tool for learning in translation classes. As a result, machine translation is regarded as a useful tool for supporting students' learning. According to the study's findings, students had a positive perception of the usage of machine translation in the translation process.